Infrastructure and Development in Rural India. (August 2017) - Ghosh, Madhusudan
This article evaluates rural infrastructure facilities in 16 major states of India, and examines their impacts on some income and non-income dimensions of rural development. Despite several public initiatives for infrastructure development in rural India, facilities continue to be poor and progress has been mostly unsatisfactory with differential performance across states. Estimates of regression coefficients of the composite indices and individual indicators of rural infrastructure reveal that improved physical and social infrastructure and livelihood opportunities enhance agricultural productivity and output, improve literacy and life expectancy, and reduce poverty and infant mortality. The results, showing the relative importance of various infrastructures, suggest that the government should prioritise additional investments in electricity, roads, irrigation, housing and telecommunications to enhance overall well-being. JEL Classification: H54, O15, O18, Q19